PSYCHIATRIC COMORBIDITIES IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - SOOD, REWA; AHUJA, GAGANDEEP; SHARMA, SHIVAM; SHARMA, DINESH DUTT; MONICA; SACHIN; SARKAR, MALAY (International Journal of Current Pharmaceutical Research, 2024)
Objective: COPD often exists with comorbidities that may have a significant impact on prognosis. Patients with COPD are predisposed to both cognitive and psychiatric disorders. Anxiety and depression are common and important comorbidities in patients with chronic obstructive pulmonary disease (COPD). Regarding this, there is a lack of data from state of Himachal Pradesh. Methods: Our study was a cross-sectional study wherein 100 patients who attended the Pulmonary Medicine outpatient clinic of IGMC, Shimla were recruited. Patients were evaluated using tools International Classification of Disease, 10threvision, MINI 6.0, Addenbrooke's Cognitive Examination, Hamilton Anxiety Rating Scale, Hamilton Depression Rating Scale. Results: About two-third (62%) of the patients were found to have psychiatric co-morbidities. The most common psychiatric co-morbidity was found to be mixed anxiety and depression in 20% of the patients followed by unspecified anxiety disorder in 12% of the patients,9% of the patients were diagnosed with dementia while 6% were found to have a major depressive disorder. As per our observation, the severity of anxiety and depressive symptoms as per the HARS scale and HAMD scales, respectively, increased as the severity of the disease increased. Conclusion: The present study shows that about two third (62%) of the patients were found to have psychiatric co-morbidities. Psychiatric comorbidities have a significant impact on quality of life, exacerbation frequency and survival. Another multicentre large observational study can be planned in the future to overcome the above problems.